The S.M OTIENO CASE ([United States] : ORO Editions, 2014)
HOK Tall Buildings is a visually engaging, accessible reference guide highlighting some of the world's most innovative tall buildings. Written by global design, architecture, engineering and planning firm HOK, the book features creative conceptual designs, projects under construction and built high-rises worldwide. Throughout the book, central themes guiding the design of these tall buildings begin to emerge. These include a focus on creating high-performance, sustainable, iconic, efficient and mixed-use structures that increase the density of urban environments. The global teams at HOK excel at designing intelligent, high-performance tall buildings that become symbols of their time and place. HOK Tall Buildings chronicles the firm's best recent designs for high-rises around the world, including: in Saudi Arabia, an iconic centrepiece that anchors a new office district; in Azerbaijan, a flame-inspired trio of towers that transforms Baku's skyline; in South Korea, an iconic residential gateway to the neighbourhoods of Incheon's dynamic northern district. Each high-rise profiled in the book is designed to blend human need with environmental stewardship, value creation, sense of place, and science and art. Gain insight into the minds and approaches of HOK's global design teams as you peruse floor plans, sketches, renderings and photographs of dozens of dynamic tall buildings. Learn how an integrated design process enables teams to solve profound functional and technical challenges while igniting the imagination. Discover how designers of tall buildings can balance internal functions with the external demands of site, climate, and culture to create memorable, sustainable structures that enrich people's lives. HOK is a global design, architecture, engineering, and planning firm. Through a network of 24 offices worldwide, HOK provides design excellence and innovation to create places that enrich people's lives and help clients succeed. For four consecutive years, Design Intelligence has ranked HOK as a leader in sustainable and high-performance design.
Abaad Tower -- Abu Dhabi National Oil Company Headquarters -- Ad Dahna Towers -- 20 Anson Road -- Bakrie Tower -- Baku Flame Towers -- Bank Headquarters for Confidential Client -- Barclays World Headquarters -- Beijing Central Business District Block Z8 -- Beijing Central Business District Block Z15 -- California State Teachers' Retirement System Headquarters -- Capital Market Authority Tower -- Century Square -- Changsha Furong District Dongpailou Complex -- Crystal Tower -- Dubai World Trade Centre -- Greenland Center Southern New City High-Rise -- Greenland Dalian East Harbor Tower -- Hexi CBD Mixed-Use Development -- Hotel competition for confidential client -- IJ-Toren -- Intercontinental Mixed-Use Tower -- Jurong Town Corporation Summit -- Keangnam Hanoi Landmark Tower -- Lotte Mooselon Tower -- 535 Mission Street -- Mongolia Democracy Tower -- Moscow City Plots 17 + 18 -- Nanjing Financial Center -- New Songdo City Mixed-Use Block D23 -- New Songdo City Mixed-Use Residential Block D22 -- Riyadh Mixed-Use Development -- Samba Bank -- Samsung Research and Development Facility 4 -- Sheraton Incheon Hotel in New Songdo City -- Suzhou SIP Tower -- US Bank Tower at 621 Capitol Mall -- West India Quay Tower -- Wuchang Riverside Business District Master Plan + Super High-Rise -- Xiamen International Centre -- Studies of function + form.
Keywords: Hellmuth, Obata & Kassabaum; Hellmuth, Obata & Kassabaum; 1900 - 2099; Tall buildings -- Exhibitions; Architecture, Modern -- 20th century -- Exhibitions; Architecture, Modern -- 21st century -- Exhibitions; Tall buildings -- Exhibitions; Architecture, Modern -- Exhibitions. -- 20th century; Architecture, Modern -- Exhibitions. -- 21st century; Exhibition catalogs; Architecture, Modern; Tall buildings; Exhibition catalogs